Tingkah laku alami burung mambruk victoria (Goura victoria) di Pulau Yapen - K. Numberi, Yusuf; Ranti, Febriza Dwi; Binur, Robi (Program Pascasarjana Universitas Papua, 2025)
ABSTRACT : The Victoria crowned pigeon (Goura cristata), known for its beautiful crest, is an endemic species of Papua and is currently listed as “Near Threatened.” Therefore, conservation efforts such as captive breeding are necessary. This pigeon has the potential to be kept in captivity due to its tamable nature; however, biological information regarding its natural behavior is still needed. This study aims to describe the natural behavior of the Victoria crowned pigeon (Goura cristata) on Yapen Island. The research was conducted in April 2024 along the Siwiri River in the eastern region of Yapen Island. A field survey method was used, with bird activity observed at three locations (downstream, midstream, and upstream). Observations were carried out over three days at each site, from 06:00 to 18:00 Eastern Indonesian Time (WIT), with 60-minute observation intervals. Bird activities were observed directly or with binoculars. The behavioral observation used the scan sampling method, and activity data were recorded using the One-Zero Sampling method. The variables observed in this study were the activity times and the percentage frequency of Victoria crowned pigeon (Goura victoria) behaviors. Five types of natural behavior were identified at the research sites: feeding (31%), vocalizing (26%), walking (16%), grooming (14%), and defecating (13%). Feeding was the most frequently observed behavior, while defecating was the least frequent. Most behaviors occurred in the morning across all three locations—downstream, midstream, and upstream. Some behaviors occurred at different times of the day, likely due to environmental differences related to habitat, topography, and abiotic factors. The conclusion of this study is that any attempt to breed the Victoria crowned pigeon in captivity must consider both biotic and abiotic factors.